2017
DOI: 10.14507/epaa.25.2891
|View full text |Cite
|
Sign up to set email alerts
|

A failed marriage between standardization and incentivism: Divergent perspectives on the aims of performance-based compensation in Shanghai, China

Abstract: Abstract:The Chinese province of Shanghai has gained international recognition as a high performing education system with strong teaching and learning outcomes. One accountability mechanism in Shanghai's education reform strategy is statewide performance-based compensation (PBC), also known as performance-or merit pay. Providing a first time account of PBC in the Shanghai context, this study investigated variance in stated and perceived aims of this policy instrument. To explore this variance, the study drew o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…First, the level of compensation is one important indicator of the professional status of any occupation (OECD, 2005(OECD, , 2018). Yet accountability reforms may limit the compensation of many teachers by introducing a merit or performancebased pay system that reallocates funding to increase salaries of a small group of high-performing teachers (Checchi & Mattei, 2021;La Londe, 2017) instead of uniformly distributing salary raises based on experience using a salary schedule. A previous comparative study of 30 OECD countries revealed that the countries that invest in experienced teachers' salaries are more likely to have a higher national achievement (Akiba et al, 2012).…”
Section: Teachers' Working Conditions and Occupational Valuementioning
confidence: 99%
“…First, the level of compensation is one important indicator of the professional status of any occupation (OECD, 2005(OECD, , 2018). Yet accountability reforms may limit the compensation of many teachers by introducing a merit or performancebased pay system that reallocates funding to increase salaries of a small group of high-performing teachers (Checchi & Mattei, 2021;La Londe, 2017) instead of uniformly distributing salary raises based on experience using a salary schedule. A previous comparative study of 30 OECD countries revealed that the countries that invest in experienced teachers' salaries are more likely to have a higher national achievement (Akiba et al, 2012).…”
Section: Teachers' Working Conditions and Occupational Valuementioning
confidence: 99%
“…In essence, a meaningful award situation in the laboratory is challenging to create because the value and consequences of awards are socially determined by interaction with other members of society (Zhou & Teo, 2017). Thus, it is hard to find suitable control groups as awards are typically not handed out randomly, and it is difficult to measure performance as awards typically reward vague outputs beyond regular duty (La Londe, 2017). Moreover, a precise definition of what constitutes an award on teachers' motivation is lacking from an academic point of view.…”
Section: Influence Of Awards On Teacher's Motivationmentioning
confidence: 99%
“…This implies that most countries have variations in implementing accountability policies across regions or schools within their education systems. The international research literature suggests that this may be the case (e.g., Han & Ye, 2017;Holloway et al, 2017;Kuiper et al, 2013;La Londe, 2017;Lim, 2016;Maroy et al, 2017;Rasmussen & Zou, 2014).…”
Section: No Pure Form Of Test-based Accountabilitymentioning
confidence: 99%
“…Responding to accountability discourses, researchers have reported theoretical debates around different forms of accountability, such as what forms of accountability ought to be considered over test-based accountability which has been dominant in education (e.g., Cranston, 2013;Fullan, Rincón-Gallardo, & Hargreaves, 2015;Sahlberg, 2007;Turnipseed & Darling-Hammond, 2015). In addition, researchers have empirically shown that there are multiple ways to achieve accountability across education systems internationally (e.g., Dorn & Ydesen, 2015;Klein, 2017;La Londe, 2017;Lim, 2016;Maroy, Pons, & Dupuy, 2017;Rasmussen & Zou, 2014;Thiel & Bellmann, 2017). Findings from these studies indicate that accountability policy implementation remains multifaceted depending on the context (Holloway et al, 2017;Klein, 2017), and therefore, the logics behind the implementation of accountability can differ based on historical backgrounds and structures of the education system.…”
Section: Introductionmentioning
confidence: 99%